(untitled) (Ustozlar uchun, 2026)
This article explores the verbalization of the concept “heart” within English and Uzbek paramiological texts, analyzing both linguistic and cultural dimensions. The heart, as a metaphorical and symbolic entity, plays a central role in emotional, moral, and spiritual expressions in both languages. Through comparative semantic and pragmatic analysis, the study reveals how the heart is conceptualized and linguistically encoded, highlighting cultural-specific features and shared human experiences. The paper further investigates the usage of heart-related verbs, idiomatic expressions, and metaphorical structures, providing insights into the interaction between language, culture, and cognition in both English and Uzbek paramiologies.